2022
DOI: 10.1007/s10126-022-10145-9
|View full text |Cite
|
Sign up to set email alerts
|

Organic Matrix and Secondary Metabolites in Nacre

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 85 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…It was reported that the organic matrix of shell nacre is comprised of the water-soluble matrix and the water-insoluble matrix. The water-soluble matrix contains the acidic proteins and polysaccharides, whereas the water-insoluble matrix contains the chitin, lipid, and the alanine and glycine rich silk-like proteins [60]. In the present study, the peaks of aragonite, proteins, carbohydrates, and water were observed, and the results were consistent with the findings of Balmain et al and Zouari et al during investigations of the organic content of the shell nacre of Pinctada maxima shells [56] and Pinctada radiata shells [61].…”
Section: Characterization Of Shell Nacre Powdermentioning
confidence: 99%
“…It was reported that the organic matrix of shell nacre is comprised of the water-soluble matrix and the water-insoluble matrix. The water-soluble matrix contains the acidic proteins and polysaccharides, whereas the water-insoluble matrix contains the chitin, lipid, and the alanine and glycine rich silk-like proteins [60]. In the present study, the peaks of aragonite, proteins, carbohydrates, and water were observed, and the results were consistent with the findings of Balmain et al and Zouari et al during investigations of the organic content of the shell nacre of Pinctada maxima shells [56] and Pinctada radiata shells [61].…”
Section: Characterization Of Shell Nacre Powdermentioning
confidence: 99%